Tracking the Elusive Fibrocyte: Identification and Characterization of Collagen‐Producing Hematopoietic Lineage Cells During Murine Wound Healing. (17th April 2014) - Suga, Hirotaka; Rennert, Robert C.; Rodrigues, Melanie; Sorkin, Michael; Glotzbach, Jason P.; Januszyk, Michael; Fujiwara, Toshihiro; Longaker, Michael T.; Gurtner, Geoffrey C.
Abstract: Fibrocytes are a unique population of circulating cells reported to exhibit characteristics of both hematopoietic and mesenchymal cells, and play an important role in wound healing. However, putative fibrocytes have been found to lose expression of hematopoietic surface markers such as CD45 during differentiation, making it difficult to track these cells in vivo with conventional methodologies. In this study, to distinguish hematopoietic and nonhematopoietic cells without surface markers, we took advantage of the gene vav 1, which is expressed solely on hematopoietic cells but not on other cell types, and established a novel transgenic mouse, in which hematopoietic cells are irreversibly labeled with green fluorescent protein and nonhematopoietic cells with red fluorescent protein. Use of single‐cell transcriptional analysis in this mouse model revealed two discrete types of collagen I (Col I) expressing cells of hematopoietic lineage recruited into excisional skin wounds. We confirmed this finding on a protein level, with one subset of these Col I synthesizing cells being CD45+ and CD11b+, consistent with the traditional definition of a fibrocyte, while another was CD45− and Cd11b−, representing a previously unidentified population. Both cell types were found to initially peak, then reduce posthealing, consistent with a disappearance from the wound site and not a loss of identifying surface marker expression. Taken together, we have unambiguously identified two cells of hematopoietic origin that are recruited to the wound site and deposit collagen, definitively confirming the existence and natural time course of fibrocytes in cutaneous healing. Stem Cells 2014;32:1347–1360